Comparison of Normal Tension Glaucoma and Preperimetric Glaucoma and Changes in Medication Use: A Multicenter Survey in Japan - Inoue K; Kunimatsu-Sanuki S; Tomita G; Ishida K (Clinical Ophthalmology)
Kenji Inoue,1 Shiho Kunimatsu-Sanuki,2 Goji Tomita,1,3 Kyoko Ishida3 1Inouye Eye Hospital, Chiyoda-Ku, Tokyo, Japan; 2Nishikasai Inouye Eye Hospital, Edogawa-Ku, Tokyo, Japan; 3Department of Ophthalmology, Toho University Ohashi Medical Center, Meguro-Ku, Tokyo, JapanCorrespondence: Kenji Inoue, Inouye Eye Hospital, 4-3 Kanda-surugadai, Chiyoda-Ku, Tokyo, 101-0062, Japan, Tel +813-3295-0911, Fax +813-3295-0917, Email 2inoue-k@inouye-eye.or.jpPurpose: This study aimed to compare clinical characteristics and treatment patterns between patients with normal tension glaucoma (NTG) and preperimetric glaucoma (PPG), assess medication trends over time, and benchmark these against a 2020 study to inform treatment strategies.Materials and Methods: During March 10– 16, 2024, 6323 outpatients diagnosed with glaucoma or ocular hypertension were enrolled in a survey conducted across 82 private practices. We compared patient characteristics and medication usage between those with NTG and PPG.Results: Among the enrolled patients, 2882 were diagnosed with NTG, and 344 were diagnosed with PPG. The average age was significantly lower in the PPG group (60.2 ± 14.3 years) than in the NTG group (69.0 ± 12.9 years, P < 0.0001). The average number of medications used was significantly higher for the NTG group (1.7 ± 1.1 drugs) than for the PPG group (0.4 ± 0.7 drugs; P < 0.0001). Monotherapy was used in 1473 patients with NTG and 96 patients with PPG. The most prescribed medications were prostanoid FP receptor agonist (FP agonists) (61.6% and 47.9% for NTG and PPG, respectively), β-adrenergic blockers (β-blockers) (18.3% and 27.1% for NTG and PPG, respectively), and prostanoid EP2 receptor agonist (EP2 agonists) (12.4% and 14.6% for NTG and PPG, respectively). FP agonist prescriptions were significantly more common in patients with NTG than in patients with PPG (P < 0.05). β-blockers and ion channel opener prescriptions were significantly more common in patients with PPG than in patients with NTG (P < 0.05). FP/β fixed-combination eye drops were the most prescribed treatment for both groups. These were used in 399 patients with NTG and 10 patients with PPG.Conclusion: NTG was more prevalent than PPG in this population. Patients with PPG were significantly younger and required fewer medications compared to those with NTG.Keywords: normal-tension glaucoma, preperimetric glaucoma, medication, multicenter survey, monotherapy